DATABASE QUALITY ANALYSIS (American Journal of Pedagogical and Educational Research, 2026)
In this article, the data itself, its storage, and processing are prioritized in database systems. In database information requirements, at certain levels, practically all properties and attributes of the ISO 9126 "Software Quality" standard can be used. In accordance with this standard, the characteristics of information quality are divided into 1) functional and 2) constructive, and the requirements for its content are formulated, which are covered in detail based on sources.